Development of Learning Video to Introduce Panting Musical Instrument in Bina Desa Program Anjir Pasar Kota II - Ahmad Naufal Rizki; Monry Fraick Nicky Gillian Ratumbuysang; Agus Hadi Utama; Hamsi Mansur (Vidya Karya, 2023)
The development of a Panting Music learning video in the MBKM Bina Desa Independent Program of FKIP ULM 2022 in Anjir Pasar Kota II Village aims to produce a product in the form of a Panting Music instrument introduction video learning media and describe the feasibility of the developed learning video. The 4D development model includes the Define, Design, Develop, and Disseminate phases. The researcher employed data collection techniques for this development, including structured observations, unstructured interviews with the village chief, questionnaires systematically distributed to the experts and participants, and documentation in photos to complement the research data. Data analysis was conducted quantitatively and descriptively. The developed media went through stages of validation, with the language validated by a language expert with a "Very Feasible" assessment category at a 95% rating, media validation by a media expert with a "Feasible" assessment category at an 85% rating, and content validation by a subject matter expert with a "Feasible" assessment category at an 80% rating. The next phase involved testing the media with students, resulting in a "Very Feasible" student responses category at a 92% rating, indicating that students could recognize and learn to play the Panting Music instrument.